2020
DOI: 10.4038/jccpsl.v25i4.8221
|View full text |Cite
|
Sign up to set email alerts
|

Perceived self-efficacy and self-managing of chronic diseases among elderly patients in a clinic setting: how capable are elders in promoting their own health?

Abstract: Introduction: Non-communicable diseases and elderly population are on the rise worldwide. It has created a massive burden on health systems, economies and society. Sri Lanka is no exception. The situation indicates the need for risk factor prevention and control through effective behaviour change programmes. Self-efficacy is postulated as fundamental to achieve behaviour change of individuals to fill the present gap of risk factor control. Objectives:To assess the perceived self-efficacy in managing chronic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…30 Limited studies support the association between perceived self-efficacy and self-care practices in the elderly with multimorbidity. 31,32 Nevertheless, the findings of this study were consistent with the one conducted in the United States, which reported that the elderly with hypertension who practiced good self-efficacy showed improved self-care behavior. 31 A similar study by Yasaratna and Wijesinghe reported that targeted health promotion interventions to improve self-efficacy had a beneficial effect on self-care practices and disease control factors such as blood pressure in the elderly with chronic diseases.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…30 Limited studies support the association between perceived self-efficacy and self-care practices in the elderly with multimorbidity. 31,32 Nevertheless, the findings of this study were consistent with the one conducted in the United States, which reported that the elderly with hypertension who practiced good self-efficacy showed improved self-care behavior. 31 A similar study by Yasaratna and Wijesinghe reported that targeted health promotion interventions to improve self-efficacy had a beneficial effect on self-care practices and disease control factors such as blood pressure in the elderly with chronic diseases.…”
Section: Resultssupporting
confidence: 89%
“…31 A similar study by Yasaratna and Wijesinghe reported that targeted health promotion interventions to improve self-efficacy had a beneficial effect on self-care practices and disease control factors such as blood pressure in the elderly with chronic diseases. 32 Effects of interventions on the increase in selfefficacy and self-care practices in the elderly have been investigated in other dimensions. Park and Chang, 33 investigated the effect of a health counseling self-management program for the elderly with multimorbidity.…”
Section: Resultsmentioning
confidence: 99%